DISRUPTION OR TRANSFORMATION? THE IMPACT OF ARTIFICIAL INTELLIGENCE ON PEDAGOGICAL COMPETENCE, ACADEMIC INTEGRITY, AND THE FUTURE OF HIGHER EDUCATION IN INDONESIA - Yuni Rindiantika; Fitria Meisarah; Muhammad Akmal Gymnastiar (ADISAM Publisher, 2026)
This article examines the dilemma of disruption versus transformation posed by generative Artificial Intelligence (AI) to Indonesian higher education, focusing on faculty pedagogical competencies, academic integrity, and the future of the education system. The research method employed was a literature review. The findings reveal that AI poses a threat of eroding critical thinking skills (a 35% decline) and fueling the rise of AI-driven plagiarism (a 30% increase), yet it also offers opportunities for transformation through adaptive learning, AI literacy as a 21st-century competency, and authentic assessment that enhances pedagogical efficiency by up to 50%. The discussion of these two main pillars underscores the need for a paradigm shift from a reactive approach (banning AI) to a proactive one (AI stewardship), with policy recommendations such as a mandatory AI literacy curriculum, national faculty training, and triple-helix collaboration. These findings are crucial for Indonesia’s “Golden Indonesia 2045” vision, ensuring that hospitality and tourism graduates remain globally competitive while upholding the academic ethics of Pancasila.